Degradable straw material and preparation method

CN122958836APending Publication Date: 2026-10-23HANYANBO BIOTECHNOLOGY (JIANGSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611180382.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

植物纤维具有比强度高、可降解、可再生等优势,但其与疏水性高分子基体的界面极性差异显著,界面结合薄弱,应力传递效率低下

Benefits of technology

通过在植物纤维表面原位矿化形成矿化纳米片层,并与天然多糖粘结剂交替堆叠构筑仿贝壳“砖泥”式层状增强结构,利用矿化纳米片层的高强度、高模量特性为复合材料提供有效的承载骨架,同时借助砖泥结构中硬-软交替的层状构型实现应力分散与能量耗散。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958836A_ABST
    Figure CN122958836A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of degradable environment-friendly materials, and particularly relates to a degradable straw material and a preparation method thereof.The technical scheme comprises the following steps: the straw material is composed of polybutylene succinate, polybutylene adipate terephthalate, thermoplastic starch, plant fiber, natural polysaccharide binder, bio-based plasticizer and compatibilizer raw materials, the surface of the plant fiber is in-situ mineralized to form mineralized nanosheet layers, and the natural polysaccharide binder is alternately stacked to construct a shell-like brick mud type layered reinforcing structure, the mineralization deposition density decreases from inside to outside, and the natural polysaccharide interface layer has a wet-sensitive peeling property.The present application realizes the synergistic unity of the mechanical properties and controllable degradation performance of the straw material, has excellent use stability and layer-by-layer ordered degradation ability after being discarded, and is environmentally friendly in the whole life cycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biodegradable and environmentally friendly materials technology, and in particular to a biodegradable straw material and its preparation method. Background Technology

[0002] Biodegradable straws, as an important alternative to traditional plastic straws, have become a research hotspot in the field of environmental materials. Currently, commercially available biodegradable straws mainly include paper straws and polylactic acid (PLA) straws. Paper straws are prone to softening and deformation when soaked in liquids; PLA straws have harsh degradation conditions and poor heat resistance, making it difficult to meet diverse consumer demands. Therefore, developing new biodegradable straw materials that combine excellent mechanical properties with controllable degradation characteristics remains a pressing technical challenge for the industry.

[0003] While PLA is one of the most commercially mature biodegradable polymers, it suffers from drawbacks such as high brittleness and poor molding stability. Polybutylene adipate / terephthalate (PBAT), as a fully biodegradable copolyester, has good flexibility and processability. Polybutylene succinate (PBS) has superior heat resistance, toughness, and processability compared to PLA, and is therefore preferred for blending with PBAT.

[0004] Introducing plant fibers into a biodegradable polymer matrix can achieve efficient utilization of biomass resources and reduce material costs. Plant fibers have advantages such as high specific strength, biodegradability, and renewability; however, the significant difference in interfacial polarity between plant fibers and the hydrophobic polymer matrix results in weak interfacial bonding and low stress transfer efficiency. Existing surface modification methods such as alkali activation and coupling agent treatment have limited effectiveness and cannot simultaneously achieve a synergistic improvement in the high strength and high toughness of composite materials. Furthermore, the hygroscopic nature of plant fibers can easily lead to performance degradation in humid and hot environments. Summary of the Invention

[0005] The purpose of this invention is to address the problems existing in the background art by proposing a biodegradable straw material and its preparation method.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a biodegradable straw material, comprising the following raw materials in parts by weight: 40-70 parts of polybutylene succinate; 15-35 parts of poly(butylene adipate / terephthalate); 5-20 parts of thermoplastic starch; 5-15 parts plant fiber; 2-8 parts of natural polysaccharide binder; 2-10 parts of bio-based plasticizer; Compatibilizer 0.5–3 parts; The natural polysaccharide binder forms a natural polysaccharide interface layer after drying on the surface of plant fibers; The plant fiber surface is mineralized in situ to form a mineralized nanosheet layer. Based on the dry weight of the plant fiber, the deposition amount of the mineralized nanosheet layer is 10% to 80% of the dry weight of the plant fiber, and the deposition density of the mineralized nanosheet layer decreases from the inside to the outside. The mineralized nanosheets and the natural polysaccharide interface layer are stacked alternately to form a brick-and-mortar-like layered reinforcement structure of no less than 3 layers. The thickness of each mineralized nanosheet layer is 20–300 nm, and the monolayer coating thickness of the natural polysaccharide interface layer is 0.2–5 μm. The adjacent mineralized nanosheet layers and the natural polysaccharide interface layer are connected by hydrogen bonds, electrostatic interactions, and / or coordination interactions. The natural polysaccharide interface layer has moisture-sensitive exfoliation properties. Under continuous humid and hot degradation environment, it absorbs moisture and expands, causing adjacent mineralized nanosheet layers to separate layer by layer, forming interlayer exfoliation channels.

[0007] Furthermore, the plant fiber is one or more of bamboo fiber, sugarcane fiber, wheat straw fiber, and wood pulp fiber.

[0008] Furthermore, the mineralized nanosheet layer is formed by the stacking of mineralized nanosheets, which are one or more of nano-calcium carbonate sheets, hydroxyapatite nanosheets, or nano-silicate sheets; the mineralized nanosheet layer is formed by in-situ growth on the surface of the plant fiber.

[0009] Furthermore, the natural polysaccharide binder is one or more of sodium alginate, chitosan, pectin, and konjac glucomannan; the compatibilizer is at least one of epoxy functionalized chain extender and titanate coupling agent.

[0010] Furthermore, the brick-and-mortar layered reinforced structure maintains its layered integrity during extrusion and is subjected to the stretching flow field of the melt to form a preferential growth orientation structure along the suction tube axis.

[0011] Furthermore, the natural polysaccharide interface layer maintains stable interlayer bonding under normal temperature conditions, and water molecules gradually diffuse from the surface of the straw to the interior, causing the natural polysaccharide interface layer to undergo hygroscopic expansion differences from the outside to the inside, triggering gradual interlayer peeling under continuous humid and hot degradation conditions.

[0012] A method for preparing a biodegradable straw material includes the following steps: S1. The plant fibers are subjected to impurity removal, cleaning and surface activation treatment, wherein the surface activation treatment is one or more of alkaline solution immersion activation, plasma treatment or silane coupling agent pretreatment. S2. The activated plant fibers are placed in a biomineralization solution to allow mineralized nanosheets to be deposited in situ on the surface of the plant fibers, followed by washing. The biomineralization solution is a solution containing mineralization precursors, which are selected from one or more of calcium salts and carbonates, calcium salts and phosphates, or magnesium salts and silicates. The concentration of active metal ions in the biomineralization solution is 0.01–0.5 mol / L, the concentration of mineralization anions is 0.01–0.5 mol / L, the pH is 7.0–9.0, the mineralization temperature is 20–40℃, and the time is 2–24 hours. S3. The mineralized plant fibers are impregnated in a natural polysaccharide solution and dried to form a natural polysaccharide interface layer. The mineralization and impregnation steps are repeated 3 to 10 times. During the alternation process, the concentration of active ions in the mineralization solution is gradually reduced or the mineralization time is shortened to form a brick-and-mortar layered reinforced structure with a radially decreasing mineralization deposition density. The mass fraction of the natural polysaccharide solution is 1% to 10%, the impregnation temperature is 25 to 60°C, the impregnation time is 10 to 60 minutes, and the drying temperature is 50 to 80°C. S4. The thermoplastic starch and bio-based plasticizer are mixed in a high-speed mixer and allowed to stand for plasticization for 4 to 12 hours. Then, the mixture is added to a twin-screw extruder for melt blending with polybutylene succinate, polybutylene adipate / terephthalate, compatibilizer, and the obtained layered reinforced plant fiber to obtain a composite material. S5. The composite material is extruded to obtain a biodegradable straw.

[0013] Furthermore, in step S2, an enzymatic mineralization method is used to cause the mineralized nanosheets to grow directionally along the length of the plant fiber; the enzymatic mineralization uses at least one of carbonic anhydrase and urease; in step S3, the mineralization treatment and natural polysaccharide impregnation are alternated 3 to 10 times, and in each alternation process, the concentration of active ions or the mineralization reaction rate in the mineralization system is gradually reduced to form a structure in which the mineralization deposition density decreases radially outward along the plant fiber.

[0014] Furthermore, in S4, the plant fibers of the brick-and-mortar layered reinforcement structure are fed into the twin-screw extruder through the side feed port. The screw section after the side feed port adopts a continuous conveying thread element and does not have a kneading block structure. The shear rate is controlled between 10 and 50 s. -1 The twin-screw extrusion temperature is 130–180℃, the screw speed is 80–300 rpm, and the residence time is 30–120 s, so that the brick-and-mortar-like layered reinforcement structure is evenly dispersed in the matrix and basically maintains the layered morphology.

[0015] Furthermore, the extruded straw in S5 is vacuum sizing, cooling and shaping, and online traction cutting to obtain the finished product. The brick-and-mortar layered reinforcement structure is oriented along the straw axis and disintegrates layer by layer from the outside to the inside in a continuous humid and hot degradation environment.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: By in-situ mineralization of plant fiber surface to form mineralized nanosheets, and alternating stacking with natural polysaccharide binder to construct a shell-like "brick and mortar" layered reinforcement structure, the high strength and high modulus properties of mineralized nanosheets provide an effective load-bearing skeleton for composite materials. At the same time, stress dispersion and energy dissipation are achieved by using the hard-soft alternating layered configuration in the brick and mortar structure.

[0017] In this invention, the natural polysaccharide interface layer exhibits moisture-sensitive exfoliation characteristics: under normal temperature conditions, the interlayer bonding is stable, but under continuous humid and hot degradation conditions, the natural polysaccharide interface layer absorbs moisture and expands, causing adjacent mineralized nanosheet layers to separate layer by layer, forming interlayer exfoliation channels. More importantly, the mineralization deposition density decreases from the inside out, with the inner layer being densely mineralized and bearing the main load-bearing function, while the outer layer is sparsely mineralized and more easily responds to degradation triggers. This gradient structural design achieves a mechanical distribution that is flexible on the outside and rigid on the inside, allowing the straw to disintegrate layer by layer in an orderly manner from the outside in under humid and hot conditions, avoiding premature loss of strength caused by the uniform swelling of traditional biodegradable materials.

[0018] In this invention, the natural polysaccharide interface layer maintains stable interlayer bonding under normal temperature conditions, ensuring the structural integrity of the straw in conventional use scenarios. Simultaneously, water molecules gradually diffuse from the surface of the straw inward, causing the natural polysaccharide interface layer to undergo differential hygroscopic expansion from the outside to the inside. Under continuous humid and hot degradation conditions, this triggers gradual delamination between the layers. This design ensures reliable performance of the straw during its normal use cycle, while enabling rapid degradation when it enters a humid and hot environment (such as composting or wet waste treatment) after disposal. This achieves an optimized balance between performance during use and degradation performance after disposal.

[0019] The polybutylene succinate, polybutylene adipate / terephthalate, thermoplastic starch, plant fibers, natural polysaccharide binders, and bio-based plasticizers used in this invention are all bio-based or biodegradable materials. The mineralized nanosheets can return to the natural mineral cycle after degradation, and the natural polysaccharides and plant fibers can be metabolized by microorganisms, resulting in no secondary pollution to the environment throughout their entire life cycle. Simultaneously, the introduction of plant fibers can significantly reduce material costs, demonstrating good economic feasibility. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the method flow of the present invention. Detailed Implementation

[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] This invention creates a shell-like "brick-and-mortar" structure by alternately constructing mineralized nanosheets and natural polysaccharide interfacial layers on the surface of plant fibers, endowing the straw with both mechanical strength and controllable degradation properties. The wet-sensitive exfoliation behavior of the natural polysaccharide interfacial layer is key to achieving layer-by-layer degradation, while the decreasing density of mineralized deposits from the inside out ensures the orderly disintegration of the structure during degradation.

[0023] Example 1

[0024] like Figure 1 As shown, the present invention proposes a biodegradable straw material and its preparation method, the preparation steps of which are as follows: S1, Plant Fiber Activation: Take 10 kg of bamboo fiber (1-3 mm in length, 10-50 μm in diameter), remove impurities, wash with water, and then soak in a 2 wt% NaOH aqueous solution at 60℃ for 2 hours for activation. Remove and wash with deionized water until neutral, then filter and dry. Alkali activation treatment effectively removes wax, pectin, and some hemicellulose from the fiber surface, increasing the surface roughness and exposing a large number of active hydroxyl groups. This provides abundant nucleation sites for subsequent in-situ mineralization, significantly improving the bonding force between the mineralized layer and the fiber.

[0025] S2, First mineralization: To prepare the biomineralization solution, CaCl2 and Na2CO3 were used as precursors. 2+ The concentration is 0.1 mol / L, CO3 2- The concentration was 0.1 mol / L, and the pH was adjusted to 8.0 with dilute hydrochloric acid or NaOH. 0.5 g / L carbonic anhydrase was added. Activated bamboo fibers were immersed in the mineralization solution and slowly stirred at 35°C for 6 hours, resulting in the in-situ growth of nano-calcium carbonate sheets on the bamboo fiber surface. After removal, the fibers were washed with deionized water to obtain primary mineralized bamboo fibers. Analysis showed that the deposition amount of the first mineralized nanosheet layer was approximately 25% of the dry weight of the fiber, with a sheet thickness of approximately 120 nm. Carbonic anhydrase can efficiently catalyze the hydration of CO2 to produce HCO3. - High concentrations of CO3 are formed locally on the fiber surface. 2- Microregions are created, inducing the directional nucleation and growth of calcium carbonate in the form of nanosheets, forming a dense layer of mineralized nanosheets arranged parallel to the fiber surface. By controlling the enzyme concentration and mineralization time, the deposition amount and thickness of the monolayer mineralization can be effectively adjusted.

[0026] S3. Repeated mineralization and impregnation to construct brick-and-mortar structures: A 4% (w / w) sodium alginate aqueous solution was prepared and heated to 40°C with stirring until homogeneous. The primary mineralized bamboo fiber was immersed in the solution and maintained at 40°C for 30 minutes. After removal, it was dried in a 60°C hot air drying oven, forming a first natural polysaccharide interface layer on the surface of the mineralized layer, with a single-layer coating thickness of approximately 1.5 μm. The sodium alginate molecular chain is rich in carboxyl and hydroxyl groups. After drying and film formation, it can coordinate with calcium ions on the surface of the mineralized nanosheets through hydrogen bonding and electrostatic interactions, tightly bonding adjacent mineralized layers. By adjusting the solution concentration and immersion time, the coating thickness of the interface layer can be precisely controlled. This thickness directly affects the interlayer bonding strength and the response rate of subsequent moisture-sensitive peeling. The mineralization and immersion steps were repeated 4 times (a total of 5 mineralizations + 5 polysaccharide immersions). The Ca content was gradually reduced during each mineralization. 2+ and CO3 2- The concentrations were successively 0.08, 0.05, 0.03, and 0.01 mol / L, and the mineralization times were successively shortened to 5, 4, 3, and 2 hours, resulting in a decreasing deposition density from the inside out. The final product was a brick-and-mortar-like layered reinforced bamboo fiber structure with five alternating layers of mineralized nanosheets and five layers of polysaccharide interface layers. The total deposition amount was 55% of the fiber's dry mass, and the outermost mineralized layer was approximately 30 nm thick. This design of progressively decreasing deposition density constructs a high-strength, high-modulus, dense mineralized framework in the inner layer, which bears the main load-bearing function. The outer mineralized layer is thinner and sparser; upon absorbing moisture, the polysaccharide interface layer is more likely to expand first, generating peeling stress, thus triggering a degradation process of layer-by-layer peeling from the outside in. This achieves a balance between mechanical properties and controllable degradation.

[0027] S4. Melt blending granulation: 12 kg of corn starch and 4 kg of bio-based plasticizer (glycerol and sorbitol mixed in a 3:1 ratio) were pre-mixed evenly in a high-speed mixer and allowed to stand at room temperature for 8 hours to plasticize, thus obtaining thermoplastic starch. During the standing plasticization process, polyol plasticizer molecules gradually penetrated into the starch granules, forming hydrogen bonds with the starch hydroxyl groups, weakening the intramolecular and intermolecular hydrogen bonding of starch, lowering the glass transition temperature of starch, and giving it thermoplastic processability. The addition of sorbitol can further inhibit starch recrystallization and improve the flexibility and long-term stability of thermoplastic starch. By weight, 55 parts of polybutylene succinate, 25 parts of polybutylene adipate / terephthalate (PBAT), 10 parts of the above thermoplastic starch, 8 parts of the above brick-and-mortar layered reinforced bamboo fiber, 1.5 parts of epoxy functionalized chain extender (ADR), and the remaining sodium alginate (to make up to 3 parts as a natural polysaccharide binder) were pre-mixed. PBS, PBAT, thermoplastic starch, and compatibilizer are fed into the twin-screw extruder through the main feed port, while fibers are fed through the side feed port. The entire screw section after the side feed port uses a continuous feed screw element without kneading blocks, and the average shear rate in this section is controlled at 25s. -1 The extrusion temperature is set at 130–180℃, the screw speed at 200 rpm, and the material residence time at approximately 60 seconds to obtain a uniformly dispersed composite material that retains its layered morphology. A side-feeding method is employed to avoid prolonged exposure of the fibers to high temperatures and shear at the main feed port, maximizing the protection of the brick-and-mortar layered structure on the fiber surface. Only a conveying thread element is installed downstream of the side feed port, and the shear rate is strictly controlled at a low level to prevent the strong shear and stretching flow field generated by the kneading blocks from breaking the mineralized layer and polysaccharide interface layer, ensuring that the fibers are uniformly dispersed in the resin matrix in a complete layered microparticle form. Water-cooled or air-cooled strip granulation is used.

[0028] S5, Extrusion Molding: The composite material is fed into a single-screw suction extruder, extruded through a tubular die, and then vacuum-sized, cooled, shaped, and cut online to form a straight suction tube. During extrusion, the melt stretching flow field causes the brick-clay structure to align axially along the suction tube. The vacuum sizing sleeve precisely controls the uniformity of the suction tube's outer diameter and wall thickness, while rapid cooling and shaping freezes and fixes the axially oriented structure. The continuous stretching effect provided by online traction further promotes the parallel alignment of the brick-clay layered reinforcement along the axial direction, fully utilizing the reinforcing effects of fibers and mineralized layers on axial stiffness and strength.

[0029] The straw has a wall thickness of 0.2 mm and an outer diameter of 6 mm. Microscopic observation revealed that the fibers maintain a brick-and-mortar layered structure with good axial orientation. Room temperature mechanical property testing showed a tensile strength of 38 MPa and a flexural modulus of 2.1 GPa, meeting the requirements for use in hot and cold beverages. Scanning electron microscopy of the cross-section showed that the interface between the layered fibers and the PBS / PBAT matrix was blurred, indicating that the compatibilizer effectively improved the bonding between the fibers and the matrix, preventing stress concentration.

[0030] Humid heat degradation test: The straw was placed in a constant temperature and humidity chamber at 60℃ and 95% relative humidity. On day 3, fine interlayer cracks began to appear on the straw surface; on day 7, obvious delamination was visible from the outside in; and on day 21, it completely disintegrated into tiny fragments, with the leachate being non-toxic. This process demonstrates the moisture-sensitive delamination characteristics of the natural polysaccharide interface layer: after absorbing moisture, the swelling force is greater than the interlayer hydrogen bonds and electrostatic forces, forming a layer-by-layer delamination channel. The experiment shows that water molecules diffuse into the straw along the microcracks on the surface and the free volume of the matrix, preferentially accumulating in the outermost natural polysaccharide interface layer, triggering a gradual hygroscopic expansion from the outside in. The expansion stress of the outer polysaccharide layer first exceeds its interfacial bonding strength with the outermost mineralized layer, leading to the outermost layer's delamination; water continues to penetrate inward, causing the next outermost layer to delaminate, and this process repeats layer by layer until the straw completely disintegrates.

[0031] Example 2

[0032] The preparation process is basically the same as in Example 1, except that: In S1, the plant fiber used is a mixture of sugarcane fiber and wood pulp fiber (mass ratio 1:1), totaling 8 kg. Sugarcane fiber has good rigidity, while wood pulp fiber has good flexibility; the mixture of the two can balance the overall processability and reinforcing effect of the fiber.

[0033] In S2, biomineralization utilizes a hydroxyapatite nanosheet system, with Ca(NO3)2 and (NH4)2HPO4 as precursors. 2+ Concentration 0.08 mol / L, PO4 3- Mineralization was carried out at a concentration of 0.05 mol / L, pH 7.8, and 30℃ for 8 hours. Enzymatic mineralization was further catalyzed by the addition of urease, which preferentially promoted the growth of nanosheets along the fiber length. The initial deposition amount was approximately 20%. Urease catalyzed the hydrolysis of urea to produce CO3. 2- and NH4 + At the same time, it provides an alkaline environment, which allows hydroxyapatite to self-assemble into nanosheets along the fiber axial template. This mineralized layer, which grows directionally along the fiber length, can further enhance the axial mechanical properties of the straw.

[0034] In S3, chitosan (dissolved in 1% acetic acid aqueous solution to prepare a 2% chitosan solution) was selected as the natural polysaccharide binder. The solution was treated six times alternately, gradually reducing the concentration of the mineralization solution, ultimately forming a brick-and-mortar structure with six mineralized layers and six polysaccharide interface layers, with a total deposition rate of 45%. The thickness of a single chitosan interface layer is approximately 0.8 μm. The amino groups on the chitosan molecular chain become protonated and positively charged under weakly acidic conditions, generating a strong electrostatic attraction with the negatively charged groups on the surface of the mineralized layer. After drying, this forms a dense polysaccharide interface layer, providing excellent interlayer bonding strength.

[0035] In S4, the base resin formulation is as follows: 60 parts PBS, 20 parts PBAT, 8 parts thermoplastic starch, 10 parts modified fiber, 5 parts tributyl acetylacetic acid plasticizer, and 2 parts titanate coupling agent. The extrusion temperature is 165–185℃, the screw speed is 150 rpm, and the shear rate after side feeding is 15 s. -1 The residence time is 90 seconds. The lower shear rate and longer residence time are suitable for fibers with relatively thick chitosan interfacial layers and multiple layers, in order to avoid structural damage and ensure sufficient dispersion of fibers in the matrix.

[0036] In S5, the finished straw also exhibited an axially oriented brick-and-mortar structure, separating layer by layer from the outside in during hygrothermal degradation. Significant stratification was observed on day 5, and complete disintegration occurred on day 28. Compared to Example 1, the moisture-sensitive peeling rate of the chitosan interface layer was slightly slower. This is related to the fact that chitosan itself has lower hygroscopicity than sodium alginate. The degradation rate can be controlled by adjusting the degree of deacetylation of chitosan or the plasticizer content.

[0037] Example 3

[0038] Differences from Example 1: In S1, 12 kg of wheat straw fiber is selected as the plant fiber.

[0039] In S2, mineralization utilizes nano-silicate sheets, with sodium silicate and magnesium chloride as precursors, to generate magnesium silicate nanosheets. Ca 2+ Replace with Mg 2+ The system (using MgCl2) also contains a small amount of Ca. 2+ To regulate the interlayer bonding.

[0040] In S3, the natural polysaccharide was prepared using a pectin solution (5% by mass). This was repeated 7 times, resulting in a total deposition of 70%. The total amount of natural polysaccharide added to the interface layer was 4 parts. Pectin is a natural polysaccharide extracted from plant cell walls. Its molecules contain abundant galacturonic acid units, and its carboxyl groups can form coordination crosslinks with magnesium and calcium ions on the surface of the mineral layer, constituting an ion-bridged polysaccharide interface layer, thus giving the interlayer higher initial bonding strength. The magnesium silicate nanosheet layer has higher hardness and thermal stability, resulting in better retention of the mineralized layer structure during high-temperature extrusion of the fiber.

[0041] In S4, the thermoplastic starch is plasticized by mixing potato starch with a bio-based plasticizer. The composite material formulation consists of 50 parts PBS, 30 parts PBAT, 15 parts thermoplastic starch, 15 parts layered reinforced wheat straw fiber, and 2 parts epoxy chain extender and titanate coupling agent compatibilizer. The screw assembly maintains a kneading-free feed downstream with a shear rate of 35 s. -1 The extrusion temperature is 175–190℃. Appropriately increasing the shear rate is necessary to match the high aspect ratio and bulk density of the straw fibers, ensuring uniform fiber dispersion in the matrix without agglomeration, while simultaneously maintaining the integrity of the brick-and-mortar structure.

[0042] In S5, the straw is obtained by extrusion molding. Its properties are: tensile strength 42MPa, and complete delamination inside and outside after 15 days of wet heat degradation.

[0043] Comparative Example 1 Similar to Example 1, but in S2 and S3, the plant fibers only underwent ordinary activation treatment without mineralization and alternating polysaccharide deposition, i.e., no brick-and-mortar layered structure. In S4, bamboo fiber, PBS, PBAT, thermoplastic starch, etc., were directly blended and extruded in the same proportion. The straw obtained in S5 had slightly lower mechanical properties (tensile strength 30 MPa). In the hydrothermal degradation test, it showed uniform swelling and erosion, without obvious layer-by-layer peeling from the outside to the inside. On day 30, it only disintegrated into larger blocks, and the degradation rate was significantly lower than that of Example 1. This indicates that without the brick-and-mortar layered reinforcement structure, the straw degradation depends on the overall hydrolysis of the resin matrix and microbial erosion, lacking directional peeling channels, and cannot achieve rapid and controllable layer-by-layer disintegration.

[0044] Comparative Example 2 Using the raw materials and formulation of Example 1, but adding all fibers from the main feed port during S4 twin-screw extrusion, and setting strong kneading blocks in the fiber feeding section of the screw assembly, with a shear rate greater than 100s. -1 As a result, the fiber-reinforced brick structure was severely damaged, with the mineralized nanosheets and polysaccharide interface layer breaking apart and failing to maintain a layered structure. No complete layered stacking was observed in the cross-section of the extruder after S5 extrusion, indicating that the hydrothermal degradation behavior shifted to overall disintegration rather than orderly layer-by-layer peeling. The intense shearing caused the mineralized layer and polysaccharide interface layer to peel and fragment, irreversibly damaging the brick structure and causing it to lose its layered characteristics. Therefore, the controlled degradation pattern of layer-by-layer peeling from the outside in could not be reproduced, demonstrating the criticality of low-shear processing technology in protecting the fiber microstructure.

[0045] Based on the above, it can be concluded that this invention constructs a biomimetic brick-and-mortar structure on the surface of a single plant fiber by alternately stacking mineralized nanosheets and natural polysaccharide interface layers. The moisture-sensitive properties of the natural polysaccharide interface layer ensure the structural integrity of the straw during use at room temperature. Under humid and hot conditions, water molecule diffusion causes the polysaccharide layer to expand, generating interlayer stress that leads to the separation of adjacent mineralized layers, forming a progressive peeling channel from the surface inward, accelerating degradation and making it controllable. The radially decreasing mineralization density design ensures that the inner layer has a higher mineralization degree to maintain initial strength, while the sparse mineralization of the outer layer facilitates the initiation of peeling. This gradient structure achieves a "soft outside, rigid inside" mechanical distribution. The outer layer responds preferentially to degradation triggering, while the inner layer continuously provides support, avoiding premature loss of strength and ensuring reliable performance of the straw throughout its entire service life. The extrusion process uses side feeding and low-shear conveying, effectively protecting the brick-and-mortar structure and aligning it along the straw's axial direction under melt stretching, improving axial stiffness. This straw possesses sufficient mechanical properties, good biodegradability, and environmental safety. In addition, all raw materials are bio-based or biodegradable. The mineralized nanosheets can return to the natural mineral cycle after degradation, and the natural polysaccharides and plant fibers can be metabolized by microorganisms. There is no secondary pollution to the environment throughout the entire life cycle.

[0046] The above specific embodiments are merely several further embodiments of the present invention. Based on the technical solutions of the present invention and the relevant teachings of the above embodiments, those skilled in the art can make various alternative improvements and combinations to the above specific embodiments.

[0047] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A biodegradable straw material, characterized in that, Including the following parts by weight of raw materials: 40-70 parts of polybutylene succinate; 15-35 parts of poly(butylene adipate / terephthalate); 5-20 parts of thermoplastic starch; 5-15 parts plant fiber; 2-8 parts of natural polysaccharide binder; 2-10 parts of bio-based plasticizer; Compatibilizer 0.5–3 parts; The natural polysaccharide binder forms a natural polysaccharide interface layer after drying on the surface of plant fibers; The plant fiber surface is mineralized in situ to form a mineralized nanosheet layer. Based on the dry weight of the plant fiber, the deposition amount of the mineralized nanosheet layer is 10% to 80% of the dry weight of the plant fiber, and the deposition density of the mineralized nanosheet layer decreases from the inside to the outside. The mineralized nanosheets and the natural polysaccharide interface layer are stacked alternately to form a brick-and-mortar-like layered reinforcement structure of no less than 3 layers. The thickness of each mineralized nanosheet layer is 20–300 nm, and the monolayer coating thickness of the natural polysaccharide interface layer is 0.2–5 μm. The adjacent mineralized nanosheet layers and the natural polysaccharide interface layer are connected by hydrogen bonds, electrostatic interactions, and / or coordination interactions. The natural polysaccharide interface layer has moisture-sensitive exfoliation properties. Under continuous humid and hot degradation environment, it absorbs moisture and expands, causing adjacent mineralized nanosheet layers to separate layer by layer, forming interlayer exfoliation channels.

2. The biodegradable straw material according to claim 1, characterized in that: The plant fiber is one or more of bamboo fiber, sugarcane fiber, wheat straw fiber, and wood pulp fiber.

3. The biodegradable straw material according to claim 1, characterized in that: The mineralized nanosheet layer is formed by the stacking of mineralized nanosheets, which are one or more of nano-calcium carbonate sheets, hydroxyapatite nanosheets, or nano-silicate sheets; the mineralized nanosheet layer is formed by in-situ growth on the surface of the plant fiber.

4. The biodegradable straw material according to claim 1, characterized in that: The natural polysaccharide binder is one or more of sodium alginate, chitosan, pectin, and konjac glucomannan; the compatibilizer is at least one of epoxy functionalized chain extender and titanate coupling agent.

5. The biodegradable straw material according to claim 1, characterized in that: The brick-and-mortar layered reinforcement structure maintains its layered integrity during extrusion and is subjected to the stretching flow field of the melt to form a preferential growth orientation structure along the suction tube axis.

6. The biodegradable straw material according to claim 1, characterized in that: The natural polysaccharide interface layer maintains stable interlayer bonding under normal temperature conditions, and water molecules gradually diffuse from the surface of the straw to the interior, causing the natural polysaccharide interface layer to undergo hygroscopic expansion differences from the outside to the inside, triggering gradual interlayer peeling under continuous humid and hot degradation conditions.

7. A method for preparing a biodegradable straw material, characterized in that, Includes the following steps: S1. The plant fibers are subjected to impurity removal, cleaning and surface activation treatment, wherein the surface activation treatment is one or more of alkaline solution immersion activation, plasma treatment or silane coupling agent pretreatment. S2. The activated plant fibers are placed in a biomineralization solution to allow mineralized nanosheets to be deposited in situ on the surface of the plant fibers, followed by washing. The biomineralization solution is a solution containing mineralization precursors, which are selected from one or more of calcium salts and carbonates, calcium salts and phosphates, or magnesium salts and silicates. The concentration of active metal ions in the biomineralization solution is 0.01–0.5 mol / L, the concentration of mineralization anions is 0.01–0.5 mol / L, the pH is 7.0–9.0, the mineralization temperature is 20–40℃, and the time is 2–24 hours. S3. The mineralized plant fibers are impregnated in a natural polysaccharide solution and dried to form a natural polysaccharide interface layer. The mineralization and impregnation steps are repeated 3 to 10 times. During the alternation process, the concentration of active ions in the mineralization solution is gradually reduced or the mineralization time is shortened to form a brick-and-mortar layered reinforced structure with a radially decreasing mineralization deposition density. The mass fraction of the natural polysaccharide solution is 1% to 10%, the impregnation temperature is 25 to 60°C, the impregnation time is 10 to 60 minutes, and the drying temperature is 50 to 80°C. S4. The thermoplastic starch and bio-based plasticizer are mixed in a high-speed mixer and allowed to stand for plasticization for 4 to 12 hours. Then, the mixture is added to a twin-screw extruder for melt blending with polybutylene succinate, polybutylene adipate / terephthalate, compatibilizer, and the obtained layered reinforced plant fiber to obtain a composite material. S5. The composite material is extruded to obtain a biodegradable straw.

8. The method for preparing a biodegradable straw material according to claim 7, characterized in that: In step S2, an enzymatic mineralization method is used to make the mineralized nanosheets grow in a directional manner along the length of the plant fiber; the enzymatic mineralization uses at least one of carbonic anhydrase and urease; in step S3, the mineralization treatment and natural polysaccharide impregnation are alternated 3 to 10 times, and in each alternation process, the concentration of active ions or the mineralization reaction rate in the mineralization system is gradually reduced to form a structure in which the mineralization deposition density decreases radially outward along the plant fiber.

9. The method for preparing a biodegradable straw material according to claim 7, characterized in that: In S4, the plant fibers of the brick-and-mortar layered reinforcement structure are fed into the twin-screw extruder through the side feed port. The screw section after the side feed port uses a continuous conveying thread element and does not have a kneading block structure. The shear rate is controlled between 10 and 50 s. -1 The twin-screw extrusion temperature is 130–180℃, the screw speed is 80–300 rpm, and the residence time is 30–120 s, so that the brick-and-mortar-like layered reinforcement structure is evenly dispersed in the matrix and basically maintains the layered morphology.

10. The method for preparing a biodegradable straw material according to claim 7, characterized in that: The extruded straw in S5 is vacuum sizing, cooling and shaping, and online traction cutting to obtain the finished product. The brick-and-mortar layered reinforcement structure is oriented along the straw axis and disintegrates layer by layer from the outside to the inside in a continuous humid and hot degradation environment.